Smart and sustainable: collecting urban transport and mobility innovation in the 2020s - Meredith Greiling (Science Museum Group Journal, 2022)
How can museums collect transport objects to reflect the changes that we can see happening on the streets around us today? Much of what is changing relates to behaviour and integrated transport systems, both of which lack material ‘objects’ to collect. Some transport changes might be more easily acquired for the historic collection – the arrival of on-street hire bikes, for example – but much of what is different with the emerging systems is about attitudes, behaviour and the use of smart technology.